2010
DOI: 10.1016/j.jnucmat.2010.06.011
|View full text |Cite
|
Sign up to set email alerts
|

The fracture strength of TRISO-coated particles determined by compression testing between soft aluminium anvils

Abstract: Abstract:Compression testing of tri-isotropic (TRISO) carbon/silicon carbide-coated fuel particles between anvil materials with a wide range of hardnesses was investigated. During compression testing, the particle produces a hardness impression before it fractures. For subsequent measurements, the same position can therefore not be used.A special testing machine was designed to use the same set of anvils for testing more than one specimen. By each time positioning a particle at a slightly different position be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The SiC layer, however, has a number of other important functions. For example, it also provides mechanical support and structural rigidity to the coated particle [83,84] even under conditions of thermal shocks [85] which occurs during the operation of a pebble bed modular reactor. This means that there must be strong bonding between the SiC layers and its two neighbouring PyC layers as discussed earlier.…”
Section: Ipycmentioning
confidence: 99%
See 1 more Smart Citation
“…The SiC layer, however, has a number of other important functions. For example, it also provides mechanical support and structural rigidity to the coated particle [83,84] even under conditions of thermal shocks [85] which occurs during the operation of a pebble bed modular reactor. This means that there must be strong bonding between the SiC layers and its two neighbouring PyC layers as discussed earlier.…”
Section: Ipycmentioning
confidence: 99%
“…The initial oxidation of Si-rich 3C-SiC(100) (3×2) surface (and also the 6H-SiC(0001)-(3×3) and the 4H-SiC(0001)-(3×3) reconstructed surfaces [88 -91]) shows a very high reactivity rate -approximately three orders of magnitude above those of silicon surfaces [87,92,93]. The other Siterminated reconstructed surface of 3C-SiC and also the other hexagonal SiC polytypes and their surfaces [89] require high oxygen exposures and high temperatures for oxide formation [83].…”
Section: Ipycmentioning
confidence: 99%
“…The fracture strength was determined by the recently developed method by Van Rooyen et al [9] by compressing the CPs between soft anvils. Finite Element Analysis (FEA) modelling was used to quantify the stress to which the particle was subjected [9].…”
Section: Introductionmentioning
confidence: 99%
“…The fracture strength was determined by the recently developed method by Van Rooyen et al [9] by compressing the CPs between soft anvils. Finite Element Analysis (FEA) modelling was used to quantify the stress to which the particle was subjected [9]. The results by Van Rooyen et al [9] showed that the removal of the outer layer of PyC by decarburization, still gave results comparable with the results obtained with the O-PyC layer intact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation